1996
DOI: 10.1074/jbc.271.3.1797
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the cDNA for a Novel Photoreceptor Protein

Abstract: A subtractive cDNA cloning strategy was used to isolate a 1381-base pair human retina-specific cDNA, human retinal gene 4 (HRG4), which hybridized to a 1.4-kilobase message in the retina and encoded a 240-amino acid acidic protein with a calculated molecular mass of 26,964 Da. The proximal 1 ⁄4 of the conceptual protein sequence was rich in glycine (18%) and proline (20%), had a predicted secondary structure of turns, and showed a loose similarity (19 -24%) to various ␣-collagen sequences, while the distal 3 ⁄… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…An example of this is glutamine synthetase (seq#8), which we isolated in our current screen and has been previously observed to be expressed in Xenopus during neural development (Hatada et al, 1995), regeneration (Tazaki et al, 2005), and following major burn injuries (Abcouwer et al, 1997). Another clone that we identified from our cDNA subtraction analysis, unc-119 (seq#29), which was originally identified as a mutation that affects nematode locomotion (Maduro and Pilgrim, 1995), has been shown to be highly conserved in metazoans (Higashide et al, 1996;Swanson et al, 1998;Maduro et al, 2000), and has also been suggested to play a role in the development of the nervous system of the zebrafish (Manning et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…An example of this is glutamine synthetase (seq#8), which we isolated in our current screen and has been previously observed to be expressed in Xenopus during neural development (Hatada et al, 1995), regeneration (Tazaki et al, 2005), and following major burn injuries (Abcouwer et al, 1997). Another clone that we identified from our cDNA subtraction analysis, unc-119 (seq#29), which was originally identified as a mutation that affects nematode locomotion (Maduro and Pilgrim, 1995), has been shown to be highly conserved in metazoans (Higashide et al, 1996;Swanson et al, 1998;Maduro et al, 2000), and has also been suggested to play a role in the development of the nervous system of the zebrafish (Manning et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…A genomic clone containing the murine orthologue of HRG4 gene was isolated from a 129 SvJ mouse genomic library (Stratagene, La Jolla, CA) by hybridization screening using a rat HRG4 (RRG4) cDNA as probe (Higashide et al, 1996). The 129 SvJ library was used to obtain a mouse gene clone with minimal difference to the target gene of homologous recombination in the embryonic stem (ES) cells of 129 SvJ lineage.…”
Section: Cloning Of the Mouse Hrg4 Genementioning
confidence: 99%
“…Two million lambda Fix II clones from the 129 SvJ mouse genomic library (Stratagene, La Jolla, CA) were plated out and screened by hybridization with a rat HRG4 (RRG4) cDNA probe using standard procedures (Higashide et al, 1996;Sambrook and Fritsch, 1989). Positive clones were purified through multiple picking and hybridization screening, and characterized by restriction mapping and DNA sequencing.…”
Section: Cloning Of the Mouse Hrg4 (Mrg4) Genementioning
confidence: 99%
See 1 more Smart Citation
“…1) is a mammalian ortholog of the Caenorhabditis elegans protein unc119 and essential for normal vision and synaptic transmission at photoreceptor synapses (1)(2)(3). Munc119/RG4 was initially identified by a differential display screen and shown to be expressed at high levels in photoreceptor synapses (1)(2)(3).…”
mentioning
confidence: 99%